👤

Complete the equation by completing the square. 1. x² + 6x=-5 2. x + 6x -7=0​

Sagot :

[tex]\huge\bold\orange{Answer}[/tex]

✏️[tex]{\orange{\rule{250pt}{1pt}}}[/tex]

1.

+6x=-5

x²-6x-5=0

x²-6x-5=0x²-6x=5

x²-6x-5=0x²-6x=5(x²-6x+9)=5+9

x²-6x-5=0x²-6x=5(x²-6x+9)=5+9(x-3)²=14

x²-6x-5=0x²-6x=5(x²-6x+9)=5+9(x-3)²=14√(x-3)²=√14

x²-6x-5=0x²-6x=5(x²-6x+9)=5+9(x-3)²=14√(x-3)²=√14x-3=±√14

x-3=√14

x-3=√14x1=3+√14

[ x-3=-√14, x2=3-√14 ]

✏️[tex]{\orange{\rule{250pt}{1pt}}}[/tex]

~Dekalidad

#CheckMate